Confinement of Fe–Al-PMOF catalytic sites favours the formation of pyrazoline from ethyl diazoacetate with an unusual sharp increase of selectivity upon recycling. Issue 73 (24th August 2018) - Abeykoon, Brian; Devic, Thomas; Grenèche, Jean-Marc; Fateeva, Alexandra; Sorokin, Alexander B.
Abstract : Catalysis inside a porphyrinic MOF resulted in the formation of pyrazoline from ethyl diazoacetate which was not observed in the presence of a homogeneous iron porphyrin. Abstract : The catalytic properties of a chemically stable iron porphyrin MOF were evaluated in a reaction with ethyl diazoacetate. In contrast to its homogeneous counterpart, an Fe-porphyrin-MOF features a different reaction pathway leading to the formation of pyrazoline due to the confinement of catalytic sites within the MOF network. Unexpectedly, a sharp increase of the selectivity from 35% (run 1) to 86% (run 5) occurs upon catalyst recycling.